A stochastic representation theorem with applications to optimization and obstacle problems - Peter Bank; Nicole El Karoui (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
We study a new type of representation problem for optional processes with connections to singular control, optimal stopping and dynamic allocation problems. As an application, we show how to solve a variant of Skorohod's obstacle problem in the context of backward stochastic differential equations.
urn:nbn:de:kobv:11-10048488
Keywords: 330; inhomogeneous convexity; Gittins index